Ethnonationalism and White immigration attitudes. Issue 1 (25th June 2021) - Thompson, Jack
Abstract: In this article, I explore how much of White Americans' opposition to immigration—opposition that is often grounded in fears of the threat that immigration poses to the robustness of America's national identity—is shaped by ethnonationalism, a set of beliefs concerning which traits are important for being a "true" American. Drawing on data from the 2016 American National Election Studies (ANES), I examine how ethnonationalism shapes White Americans' attitudes towards immigrants. I find that ethnonationalism is positively associated with anti‐immigrant attitudes among Whites, with the effect size of my ethnonationalism measure being larger than that of any other variable in my ordinary least squares (OLS) regression model. Critically, this includes a number of variables that are already known to be strongly predictive of White attitudes towards immigration, such as Republican partisanship. Beyond anti‐immigrant attitudes, I also find that ethnonationalism also predicts support for policies that would restriction immigration.